(untitled) (Research, Society and Development, 2020)
Objective: Investigate the epidemiological profile of tuberculosis in the city of Imperatriz, Maranhão state between 2014 and 2015. Metodology: This is a descriptive epidemiological study with a quantitative approach. Data from the tuberculosis notification sheets of the municipality of Imperatriz byre SINAN were collected between 2014 and 2015, obtaining absolute and relative values of the variables analyzed. Results: The most affected patients were male, color / brown race, low schooling, with age less than or equal to 40 years, the majority were new cases with pulmonary form, the findings evidenced that sputum smear examination was more accomplished than culture and histopathology in reported cases, and HIV testing was done in most cases. Conclusions: The research revealed a profile of the population affected by the disease, evidencing important epidemiological aspects to be considered in terms of management and organization of health services for equity in access and social development.